2022
DOI: 10.1371/journal.pone.0276721
|View full text |Cite|
|
Sign up to set email alerts
|

Greater volumes of a callosal sub-region terminating in posterior language-related areas predict a stronger degree of language lateralization: A tractography study

Abstract: Language lateralization is the most intriguing trait of functional asymmetry for cognitive functions. Nowadays, ontogenetic determinants of this trait are largely unknown, but there are efforts to find its anatomical correlates. In particular, a white matter interhemispheric connection–the corpus callosum–has been proposed as such. In the present study, we aimed to find the association between the degree of language lateralization and metrics of the callosal sub-regions. We applied a sentence completion fMRI t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
4
1
Order By: Relevance
“…Notably, our shape analysis revealed no significant correlation between shape measures of the callosal tracts and language lateralisation, consistent with Westerhausen et al (2006), who proposed that the microstructural organization, rather than the macrostructure, of the corpus callosum indicates functional language lateralisation. These findings differ from a recent study by Karpychev et al (2022), which found that greater volumes of a posterior corpus callosum subregion were associated with a more substantial degree of language lateralisation (both RLD and LLD). Although subtle or no significant association was observed between long-range association fibres (including the inferior fronto-occipital fasciculus, superior longitudinal fasciculus, and uncinate fasciculus) and LQ in line with previous research (Delgado-Fernández et al, 2020; James et al, 2015; Silva & Citterio, 2017), a few earlier studies have reported conflicting results.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Notably, our shape analysis revealed no significant correlation between shape measures of the callosal tracts and language lateralisation, consistent with Westerhausen et al (2006), who proposed that the microstructural organization, rather than the macrostructure, of the corpus callosum indicates functional language lateralisation. These findings differ from a recent study by Karpychev et al (2022), which found that greater volumes of a posterior corpus callosum subregion were associated with a more substantial degree of language lateralisation (both RLD and LLD). Although subtle or no significant association was observed between long-range association fibres (including the inferior fronto-occipital fasciculus, superior longitudinal fasciculus, and uncinate fasciculus) and LQ in line with previous research (Delgado-Fernández et al, 2020; James et al, 2015; Silva & Citterio, 2017), a few earlier studies have reported conflicting results.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have investigated the relationship between characteristics of white matter and HLD, focusing on morphometric features (Josse et al, 2008; Karpychev et al, 2022; Westerhausen et al, 2006). However, no studies have combined tractography shape analysis with functional data in healthy individuals to examine the connection between geometric features of tracts and language lateralisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been explained by asymmetric callosal fibers favoring transfer toward the left temporal region (Andoh et al, 2015). Karpychev et al (2022) recently bring new argument to the role of the corpus callosum in language lateralization, showing the relation between language lateralization in adults and the volume of the temporal callosal fibers in the splenium measured with constrained spherical deconvolution (CSD). As the left posterior temporal region is notably involved in phonetic coding and intelligibility (Hickok & Poeppel, 2007;Vagharchakian et al, 2012), these results underline the centrality of this region in auditorylinguistic networks from the outset.…”
Section: Discussionmentioning
confidence: 99%
“…An asymmetric inter-hemispheric between auditory regions through the corpus callopsum has been described in infants (Adibpour et al, 2020) and adults (Andoh et al, 2015; Gotts et al, 2013; Karpychev et al, 2022). In adults, repetitive stimulation of the right auditory cortex with TMS modulates its connectivity with the left contralateral temporal cortex but not the reverse.…”
Section: Discussionmentioning
confidence: 99%